The Influence of Accessibility and Responsivity of Officers on Community Satisfaction - Ibrahim, Ely; Darman, Darman; Sari, Dwi Oktia; Setiawan, Lukman (The Eastasouth Management and Business, 2024)
This research explains the influence of officer accessibility and re-sponsiveness on community satisfaction, by observing 50 communi-ty samples. Data were analysed using PLS-SEM techniques via SMARTPLS version 3 software. Samples were selected and collected through purposive sampling and distributed via online question-naire via Google form. The results show that Accessibility has an insignificant effect, with a TStatistic value of 0.037 and P Values of 0.970, while Officer Responsiveness has a significant effect, with a TStatistics value of 4.953 and P Values of 0.000 on Community Satis-faction.